Realigning the focus of plagiarism detection using plagiarismdetect.com. - Sabapathy, Elangkeeran; Abd Rahim, Rozlan; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
The purpose of this article is to examine the extent to which plagiarismdetect.com, an internet help/tool to detect plagiarism helps academicians tackle the ever-growing problem of plagiarism. Concerned with term papers, essays and most of the time with full-blown research reports, a tool like plagiarismdetect.com may provide an avenue to ease the burden of detecting plagiarism. As far as plagiarism is concerned, not being computer savvy itself can be a bane when faced with students who appear like wizards in the area of managing information from the internet. Tracking down plagiarists is made easy and free by this site and it may still prove to be the nightmare that is needed to check the unprecedented unethical practices within the academic circle as well as curtail plagiarised work from students. Although some people use other people’s material as “seed” for generating ideas and to support their own, the point where material ownership becomes plagiarised material is also another area that a detection tool for plagiarism should be able to handle. Other than this, paraphrasing has always been the solution by lecturers for consistent occurrences of students’ plagiarised work. How much of paraphrasing can be considered before it borders on plagiarism? Will plagiarismdetect.com be able to live up to its reputation as a tool to detect and to help students and academicians to turn in original pieces of work?